FRI0310 Serum Insulin-like Growth Factor-Binding Protein 2 (IGFBP2) as A Biomarker of Clinical and Histopathological Treatment Response in Lupus Nephritis. (15th July 2016) - Parodis, I.; Ding, H.; Zickert, A.; Arnaud, L.; Mohan, C.; Gunnarsson, I.
Abstract : Background: Lupus nephritis (LN) is a severe manifestation of Systemic Lupus Erythematosus (SLE). Renal biopsy is the gold standard for evaluation of renal activity and damage in LN. Evaluation of new biomarkers for non-invasive assessment of renal pathology is warranted. Insulin-like growth factor-binding protein 2 (IGFBP2) has been found to be a robust diagnostic and prognostic biomarker in malignancies. In animal models, IGFBP2 expression was increased in anti-glomerular basement membrane (anti-GBM) glomerulonephritis and MRL/lpr lupus mice. Objectives: We aimed to investigate the role of IGFBP2 in LN. Methods: Serum levels of IGFBP2 were assessed by ELISA (R&D Systems) in 64 patients with biopsy-proven active LN (52 proliferative, 12 membranous), before and after completion of induction treatment. Post-treatment renal biopsies were performed after a median time of 7.7 months. Clinical responders (CR) were defined by ≥50% reduced proteinuria, normal or ≥25% improved estimated glomerular filtration rate (eGFR), and inactive urinary sediment. Histopathological responders (HR) were defined by ≥50% improvement of renal Activity Index (AI) in post-treatment biopsies. Long-term renal outcome after a median time of 11.3 years (range: 3.3–18.8) was determined by the last eGFR. Results: Serum IGFBP2 levels decreased following induction therapy (p<0.001). Serum IGFBP2 levels decreased in both CR (p<0.001) and HR (p<0.001), but remained unchanged in clinical non-responders (CNR; p=0.44) and histopathological non-responders (HNR; p=0.16). Post-treatment, but not baseline, IGFBP2 levels were higher in CNR compared to CR (p=0.004). Serum IGFBP2 levels correlated with proteinuria, both at baseline (r=0.34, p=0.006) and post-treatment (r=0.48, p<0.001). Post-treatment, but not baseline, IGFBP2 levels correlated with Activity Index (r=0.31, p=0.015) and Chronicity Index (CI) scores (r=0.35, p=0.006) in post-treatment renal biopsies, as well as with post-treatment SLE disease activity index 2000 (SLEDAI-2K) scores (r=0.32, p=0.009). Baseline IGFBP2 levels were associated with decreases in eGFR following treatment (p=0.028); no other association was found between baseline IGFBP2 and changes in proteinuria (p=0.14), SLEDAI-2K (p=0.97), AI scores (p=0.54) or CI scores (p=0.07). Following induction treatment, patients showed improvements in eGFR (p<0.001). No correlation was found between IGFBP2 and eGFR at either baseline or post-treatment, and there was no association between baseline (p=0.48) or post-treatment (p=0.91) serum IGFBP2 levels and changes in eGFR during long-term follow-up. Conclusions: The decreases in serum IGFBP2 levels following induction therapy in responding, but not in non-responding, patients suggest serum IGFBP2 as a marker of disease activity and response to treatment in LN. Interestingly, baseline IGFBP2 levels were associated with renal function deterioration following treatment, despite an overall improvement in eGFR. Post-treatment, but not baseline, levels mirrored both global SLE activity and histopathological findings, which together with the observed correlation with proteinuria levels suggests IGFBP2 as a marker of activity in patients with history of LN and no or low-grade proteinuria. Disclosure of Interest: None declared